Konsep Taoisme Tentang Keseimbangan Antara Manusia dengan Alam dan Relevansinya dalam Ritus Hamis Batar pada Suku Mamulak Desa Meotroi, Kecamatan Laen Manen Kabupaten Malaka - Koli, Arnoldus Nofrianus; Karloman, Siprianus; Locang, Gregorius (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research focuses on the Taoist concept of balance between humans and nature, and its relevance in the Hamis Batar ritual performed by the Mamulak tribe in Meotroi Village, Laen Manen Sub-district, Malacca Regency. Taoism teaches the importance of harmony with nature as a basic principle of life. In the context of the Mamulak tribe, the Hamis Batar ritual is a manifestation of this understanding and practice of balance. This research aims to explore how Taoist values are integrated into the daily lives of the Mamulak tribe and how this ritual serves as a means to strengthen the spiritual and ecological relationship between the community and their environment. Through a qualitative approach, data was collected through interviews and participatory observation, providing deep insights into local cultural practices and beliefs.